What do we know about sibling attended birth? An integrative literature review. (August 2018) - Naber, Nora L.; Miller, Suzanne; Baddock, Sally A.
Highlights: Sibling attended birth has potential benefits for families. Children view birth as a positive, exciting and important life event. Parents view their experience as positive and report heightened family unity. In the short term, children do not show signs of trauma or severe distress. Long term effects of sibling attended birth have not been studied to date. Abstract: Objective: to consolidate existing research in the field of sibling attended birth (SAB) into a body of knowledge to inform decision-making processes and guide midwifery practice throughout the sibling attended birth experience. Design: An integrative literature review. Data Sources: CINAHL Complete, Cochrane Library, PubMed, Index New Zealand, Australia/New Zealand Reference Centre, grey literature databases Review Methods: An extensive search of five electronic databases as well as 17 grey literature databases was conducted. Abstracts of 2340 papers and full texts of 39 papers were scrutinised for inclusion criteria leading to 22 studies being included in this review. The Crowe Critical Appraisal Tool was used to facilitate a systematic quality appraisal process. Findings: This review included 22 studies (13 qualitative, 4 quantitative and 5 mixed methods). Studies were analysed using a narrative synthesis approach. Publications mainly focussed on families' motivations for choosing SAB, the preparation for the event, and the impact of SAB on children's behaviour and the infant/sibling relationship. Conclusions: This review identified that children experienced birth as a positive, exciting and important life event and parents viewed their SAB experiences as overwhelmingly positive and reported a heightened sense of family unity. Included studies did not address the long term effects of sibling attended birth, however, in the short-term, children did not show signs of trauma or severe distress, though differing levels of transient fear and anxiety were described. Implications for practice: Families could benefit from receiving evidence based information to enable an informed decision regarding their children's involvement during pregnancy, birth and the immediate postpartum. Information shared by the midwife could focus on how families can achieve an optimal SAB experience for all family members.